Edukasi Partisipatif untuk Keberlanjutan Ekosistem Pesisir: Implementasi Program Penguatan Generasi Lestari di SMK Negeri 1 Pangandaran - Dina Oktavia; Millary Agung Widiawaty; Moh. Dede; Lathifah Puji Hastuti; Kevin Muhamad Lukman; Santi Dwi Pratiwi; Sari Rabbiyani; Zalzabilla Sapphira Mushafqzaman (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The Pangandaran Nature Reserve faces increasing sustainability pressures due to intensified human activities in its surroundings. This Community Service Program (PKM) aims to enhance environmental literacy and conservation participation among students of SMK Negeri 1 Pangandaran as prospective agents of change. A total of 50 participants were involved through a participatory approach combining interactive seminars and hands-on training in organic waste composting. Evaluation results show that all participants are familiar with the Pangandaran Nature Reserve; however, understanding of its ecological and scientific functions remains limited (30%). Field visits and social media serve as the main information sources that enhance learning effectiveness. Most participants have joined conservation activities such as community clean-ups and tree planting, demonstrating positive attitudes toward environmental preservation. The program effectively strengthened understanding and fostered social capital for school-based conservation. An educative and applicative approach emphasizing experiential learning and personal responsibility proves effective in nurturing sustainable awareness of protected areas.